Pengaruh Disiplin Kerja Dan Motivasi Terhadap Produktivitas Kerja Pegawai Pada Dinas Kesatuan Polisi Pamong Praja Dan Pemadam Kebakaran Kabupaten Sidrap - Adinda Three Ainun Haris; Muh.Ichwan Musa; Uhud Dharmawan Natsir (Journal of Management and Social Sciences, 2024)
This research aims to determine the influence of work discipline and motivation on the work productivity of employees at the Sidrap Regency Civil Service Police and Fire Department. The sample in this study was 85 people, namely all employees at the Sidrap Regency Police Service and Fire Department. The data used are primary and secondary data obtained from distribution via questionnaires. The results of this research show that there is a significant influence between the variables work discipline (X1) and motivation (X2) on employee work productivity (Y) as proven through analysis of the T test and f test, where variable X has t count > t table (X1) 6.178 > 1.98932 and (X2) 2.566 > 1.98932. The results of this research also show that the calculated f value > table f (0.000 < 0.5). And R square is 35.9%.